1995
DOI: 10.1002/ppul.1950200504
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal chronic lung disease, oxygen dependency, and a family history of asthma

Abstract: We examined the relationship between a family history of asthma (FHA), neonatal chronic lung disease (CLD), and oxygen dependency in an inception cohort study of all 24- to 30-week gestation infants admitted to the sole tertiary perinatal center in Western Australia. One hundred and forty-four infants were admitted during the study period; 116 had data analyzed, 112 of whom survived to discharge. Respiratory morbidity was common and the prevalence increased with decreasing gestation. Hyaline membrane disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…To enable log transformation of zero days, one day was added to each of the scores for days on oxygen and IPPV. 27 The nonlinear relationship between FEV 1 and oxygen was modeled, using a power function of the form…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable log transformation of zero days, one day was added to each of the scores for days on oxygen and IPPV. 27 The nonlinear relationship between FEV 1 and oxygen was modeled, using a power function of the form…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that a family history of asthma predisposes to BPD 32 or that maternal bronchial hyperresponsiveness (BHR) predisposes to premature birth. 11 Hagan et al 27 recently reported that a family history of asthma increased the risk of, but did not directly cause, BPD. Wheezing itself did not contribute significantly to the variance of the expiratory flow measurements in this study, and this apparent dichotomy is probably due to the label of asthma being applied at the more symptomatic end of the wheezing range.…”
Section: Discussionmentioning
confidence: 99%
“…We also had clear evidence of an incremental increase in risk when both parents reported symptoms of bronchial hyperreactivity and this effect persisted after controlling for all confounding variables in our logistic regression analysis. Some authors have postulated that familial bronchial hyperresponsiveness might be a risk factor for idiopathic preterm labour and chronic lung disease postnatally.31 32 This correlation with neonatal chronic lung disease may relate to an increase in severity in the disease in those infants with a family history of bronchial hyperresponsiveness5 7 rather than an increase in the prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, small molecule-induced stimulation of the HIF-1 signaling cascade during hyperoxia can alleviate some of the structural deficits induced by neonatal hyperoxia exposure (2). Clinicians, therefore, might explore the relationship between oxygenation, HIF-1␣-mediated changes in inflammation, and susceptibility to chronic lung disease in preterm infants (15,33). It should be noted that the link between preterm birth and changes in allergeninduced inflammation might only be beneficial in certain conditions.…”
Section: Discussionmentioning
confidence: 97%